2009
DOI: 10.1108/14630010910940525
|View full text |Cite
|
Sign up to set email alerts
|

A framework for talent management in real estate

Abstract: PurposeThe purpose of this paper is to propose talent management, in today's competitive marketplace, is critical in organizational success. Real estate organizations are now recognizing the value in attracting and retaining the best, brightest employees in order to achieve higher than average market share and elevated profiles. In the era of the knowledge worker, “talent” – narrowly defined as a core group of leaders, technical experts and other key contributors – are quickly becoming an organization's most i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 1 publication
4
62
1
2
Order By: Relevance
“…We have identified relevant variables to explain the relationship between talent management and organization performance. Talent Management consists of five elements: attracting/recruiting, selecting, engaging, developing and retaining employees (Phillips & Roper, 2009). …”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…We have identified relevant variables to explain the relationship between talent management and organization performance. Talent Management consists of five elements: attracting/recruiting, selecting, engaging, developing and retaining employees (Phillips & Roper, 2009). …”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Furthermore, it is a way to benchmark a company with other companies and within the organisation. Previous studies have shown that the real estate industry has developed to become more service and customer-oriented (Phillips and Roper, 2009). Also taking Sandersson (2015) conclusion, the tenants' wants to have a well functioning communication with the management, should be a crucial incentive to make customer evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…It can also be a way to compare a company with other companies' results and also within the organisation. Previous studies show that the real estate industry has developed to become more service and customer oriented (Phillips andRoper, 2009 andPalm, 2013). This implies that measuring customer satisfaction should be of great interest for the industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Davies [22] bilimsel ortamda yetenek yönetimi için orijinal ve kullanışlı bir taslak çerçeve oluşturmuştur. Phillips [23] …”
Section: Yetenek Yöneti̇mi̇ (Talent Management)unclassified